Students' and lecturers' perception of osce, in Pusat Pengajian Sains Kesihatan, University Sains Malaysia Degree Nursing Programme - Emran "Mohammad Ali", Salem Kan'an (2008)
The aim of this study is to assess the perception of students and lecturers toward the utility of OSCE as a method of assessment in PPSK, USM degree nursing programme. This study was a non-experimental study involving 1 09 students and 11 lecturers from PPSK, USM degree nursing programme in the year 2007. These two groups (students and lecturers) were selected purposively from PPSK, USM degree nursing programme. Students and lecturers who did not meet pre-determined criteria were excluded. The selected groups were interviewed using structured questionnaires. The results indicate that although the OSCE was perceived as an educational benefit by 57 students (52.3%) and as fair by 66 students (60.6%) and as an educational benefit by 7 lecturers (63.6%), the students also acknowledged it as stressful (58 students (53.2%)) and by the lecturers as unfeasible (6 ,54.5%) as a form of assessment. The one-way ANOVA analysis result of the association ofthe total students' perception score of the educational benefits and stress of OSCE to the students' year of study showed that there was no significant association between students' year of study and the educational benefits perception score or the stress perception score from OSCE. However, the result also revealed there is significant association between students' year of study and the fairness perception scores. The result showed that fourth year students had lower perception scores. The result of non-parametric test (Kruskal-Wallis) of the total lecturers' perception score of the educational benefits and feasibility of OSCE for differences among · lecturers according to year of OSCE experience showed that there were no significant differences by lecturers' years ofOSCE experience. Any form of assessment has its problems or concerns. Although there are some limitations to the OSCE approach it still has its advantages and must therefore be viewed in the context of the strengths and limitations compared to other forms of assessment. This study has identified many areas for further exploration. A larger longitudinal study is needed to establish the effectiveness of OSCE within nurse education programmes.